2008
DOI: 10.1007/s00018-008-8146-7
|View full text |Cite
|
Sign up to set email alerts
|

The expression profile of TLR9 mRNA and CpG ODNs immunostimulatory actions in the teleost gilthead seabream points to a major role of lymphocytes

Abstract: The potential effects of synthetic unmethylated oligodeoxynucleotides (ODN) containing CpG motifs, mimicking bacterial DNA, has never been evaluated on the immune response in the teleost fish gilthead seabream (Sparus aurata), the most important fish species in Mediterranean aquaculture. First, binding and competition studies have demonstrated that binding is saturated and promiscuous, suggesting the participation of several receptors. Moreover, leucocyte cytotoxic (NCC) activity, production of ROIs (reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
5
26
0
Order By: Relevance
“…Among those tested, particularly ODN-1826 has the ability to induce an immune response in HK leukocytes of Atlantic cod. Such findings were also obtained in an in vitro study by Cuesta et al (2008a) in gilthead seabream HK leukocytes. For comparison with other fish species, CpG-ODN 1826 enhanced respiratory burst, induced acid phosphatase production and enhanced antibacterial activity in grass carp, Ctenopharyngodon idellus (Meng et al 2003).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Among those tested, particularly ODN-1826 has the ability to induce an immune response in HK leukocytes of Atlantic cod. Such findings were also obtained in an in vitro study by Cuesta et al (2008a) in gilthead seabream HK leukocytes. For comparison with other fish species, CpG-ODN 1826 enhanced respiratory burst, induced acid phosphatase production and enhanced antibacterial activity in grass carp, Ctenopharyngodon idellus (Meng et al 2003).…”
Section: Discussionsupporting
confidence: 70%
“…This observation was valid in other fishes too-Atlantic salmon (Jørgensen et al 2001), grass carp (Meng et al 2003), common carp, Cyprinus carpio (Tassakka et al 2006) and rainbow trout, Oncorhynchus mykiss (Shen et al 2006). Further it should be noted that the response to the CpG motifs are species-specific-CpG-ODN 1670 induced response in Atlantic salmon HK leukocytes (Jørgensen et al 2003), ODN 1668 was found to be stimulatory for gilthead seabream (Cuesta et al 2008a). We studied respiratory burst and the activities of acid phosphatase, alkaline phosphatase and myeloperoxidase to assess the role of CpG DNA in the activation of cellular processes of the innate immune responses in a cold-water fish, Atlantic cod.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This has allowed us to get a lot of information about the regulation of the seabream immune response, and concretely the NCC activity. Thus, we have shown in vitro and/or in vivo modulation of seabream NCC activity by vitamins C (Cuesta et al, 2002b), E , A (Cuesta et al, 2003b) and D3 (Cerezuela et al, 2009), chitin (Cuesta et al, 2003c;Esteban et al, 2000Esteban et al, , 2001, levamisole (Cuesta et al, 2002c), lactoferrin , melatonin (Cuesta et al, 2008a), propolis (Cuesta et al, 2005b), inulin (Cerezuela et al, 2008), unmethylated oligodeoxynucleotides (ODNs) containing cytosine-phosphodiester-guanosine (CpG) motifs (Cuesta et al, 2008b(Cuesta et al, , 2008c, probiotic bacteria Salinas et al, 2005Salinas et al, , 2006Salinas et al, , 2008, yeast (Cuesta et al, 2007;Ortuño et al, 2002;Reyes-Becerril et al, 2008;Rodríguez et al, 2003), fungi (Rodríguez et al, 2004), virus , environmental contaminants (p,p´-DDE and lindane) (Cuesta et al, 2008d) or stress factors (air exposure, crowding and anaesthetics) (Cuesta et al, 2003d). In general, we have demonstrated great NCC increments after these treatments.…”
Section: Modulation Of the Fish Cytotoxic Activitymentioning
confidence: 99%
“…is also modulated (Table 2), suggesting an increase in the CMC activity. First, the NCCRP-1 gene expression was altered after bacterial infection (Reyes-Becerril et al, 2011;Sakata et al, 2005), administration of immunostimulants (Cuesta et al, 2008b(Cuesta et al, , 2008dLazado et al, ;Reyes-Becerril et al, 2008), exposure to contaminants (Cuesta et al, 2008d) or bacterial vaccination (Caipang et al, 2008), depending on the fish species, tissue, time and dose of exposure, and suggests a parallel effect of fish NCC activity. Perforin gene expression is usually up-regulated after immunization of ginbuna crucian carp with tumor cells (Toda et al, 2011a), after PHA-L (Phaseolus vulgaris leucoagglutinin) stimulation of trout CD8 + cells (Takizawa et al, 2011), after VHSV infection of RTS11 cell line (Ordás et al, 2011) and after viral infection or DNA vaccination in rainbow trout (unpublished data), whilst down-regulated after cadmium exposure (Auslander et al, 2008).…”
Section: Modulation Of the Fish Cytotoxic Activitymentioning
confidence: 99%